Increased Uric Acid, Gamma-Glutamyl Transpeptidase and Alkaline Phosphatase in Early-Pregnancy Associated With the Development of Gestational Hypertension and Preeclampsia - Chen, Yequn; Ou, Weichao; Lin, Dong; Lin, Mengyue; Huang, Xiru; Ni, Shuhua; Chen, Shaoxing; Yong, Jian; O'Gara, Mary Clare; Tan, Xuerui; Liu, Ruisheng (Frontiers in Cardiovascular Medicine, 2021)
Background: Previous studies have reported that biomarkers of liver injury and renal dysfunction were associated with hypertensive disorders of pregnancy (HDP). However, the associations of these biomarkers in early pregnancy with the risk of HDP and longitudinal blood pressure pattern during pregnancy were rarely investigated in prospective cohort studies. Methods: A total of 1,041 pregnant women were enrolled in this prospective cohort study. BP was assessed in four stages throughout pregnancy. The following biomarkers were measured at early pregnancy before 18 weeks gestation: lactate dehydrogenase (LDH), aspartate aminotransferase to alanine aminotransferase ratio (AST/ALT), gamma-glutamyl transpeptidase (GGT), alkaline phosphatase (ALP), uric acid (UA), and estimated glomerular filtration rate (eGFR). Linear mixed-effects and logistic regression models were used to examine the associations of these biomarkers with longitudinal BP pattern during pregnancy and HDP incidence, respectively. Results: In unadjusted models, higher serum UA, GGT, ALP, and LDH levels, as well as lower eGFR and AST/ALT, were associated with higher BP levels during pregnancy and an increased risk of HDP. After adjustment for maternal age, pre-pregnancy BMI and other potential confounders, UA, GGT, ALP, and LDH remained positively associated with both BP and HDP. However, eGFR and AST/ALT were not associated with HDP after adjusting for potential confounders. When including all 6 biomarkers simultaneously in multivariable analyses, increased UA, GGT, and ALP significantly associated with gestational hypertension and preeclampsia. Conclusion: This study suggests that increased UA, GGT, and ALP in early-pregnancy are independent risk factors of gestational hypertension and preeclampsia.